A Comparison of Dialogic Reading, Modeling, and Dialogic Reading Plus Modeling. Issue 2 (April 2020) - Coogle, Christan Grygas; Parsons, Allison Ward; La Croix, Leslie; Ottley, Jennifer R.
Abstract : The authors used an alternating treatment, single-case design to determine the effect of dialogic reading, modeling, and dialogic reading plus modeling on the expressive vocabulary identification of 2 preschool children identified with autism spectrum disorder. Their preschool teacher implemented each of the conditions within the daily routines of the classroom. Each condition demonstrated effectiveness; however, the dialogic reading condition had the most robust effect on both of the children's labeling of target vocabulary words.